Neurological recovery and efficacy of posterior per‐cutaneous pedicle internal fixation combined with full‐endoscopic debridement and intravertebral bone grafting in the treatment of thoracolumbar tuberculosis. Issue 4 (28th December 2020) - Wang, Zheng‐Meng; Yuan, Hao; He, Qing; Cao, Guang‐Ru; Chen, Tai‐Yong; Kong, Wei‐Jun; Ao, Jun; Xin, Zhi‐Jun; Cai, Yu‐Qiang
Abstract : Background: The traditional open surgery in the treatment of spinal tuberculosis has the disadvantages of greater trauma, with more intraoperative bleeding and long postoperative hospitalization days. With the development of minimally invasive spine surgery (MISS) and spinal endoscopic systems, the minimally invasive spine surgery technique was increasingly being used by surgeons because it minimizes trauma, and patients experience faster recovery. The purpose of this study was to discuss the efficacy and clear indications of this treatment. Methods: The clinical data of thirty‐one patients with thoracolumbar tuberculosis treated by posterior percutaneous pedicle screw fixation combined with full‐endoscopic debridement and intravertebral bone grafting were analyzed retrospectively. The preoperative and postoperative imaging manifestations and clinical results were compared, and the postoperative complications were observed with a follow‐up for more than 1 year. Results: Compared with values before the operation, the visual analogue scale (VAS) score and Oswestry Disability Index (ODI) score were significantly decreased at 3 months after operation and at the last follow‐up. The erythrocyte sedimentation rate (ESR) and C‐reactive protein (CRP) level were decreased at 3 months after surgery and at the last follow‐up, and no significant reduction was observed in the Cobb angle at 3 months after operation or at the last follow‐up. In addition, imaging examinations showed that the necrotic material in vertebral bodies was adequately resected. Conclusion: One‐stage percutaneous pedicle screw fixation combined with full‐endoscopic focus debridement and intravertebral bone grafting can achieve the purpose of removing the focus of thoracolumbar tuberculosis, restoring neurological function, and reconstructing spinal stability. It was a safe and feasible surgical method and its surgical indications were clarified.